Nutrients vs. turbulence, and the future of Arctic Ocean primary production - Randelhoff, Achim; Sundfjord, Arild; Fer, Ilker; Reigstad, Marit; Tremblay, Jean-Eric; Guthrie, John D. (Norsk Polarinstitutt, 2016)
Poster no. B7 from Forum for Arctic Modeling & Observational Synthesis (Woods Hole Oceanographic Institution, 2-4 November 2016. This poster presents estimates of nitrate fluxes in the Arctic Ocean and speculates on the associated primary production in a future climate.